The HAWK Highway: A Vertical Model for Student IEP Participation. (May 2015) - Quann, Monica; Lyman, Jennifer; Crumlish, Jamie; Hines, Sally; Williams, Lynn; Pleet-Odle, Amy; Eisenman, Laura
Special educators at an inclusive career-technical high school created a model to support annually increasing expectations for self-determination and levels of student participation in Individualized Education Program (IEP) planning and implementation. The grade-specific components of the model and supporting context are described. Students were observed to gain confidence in IEP participation and extend their self-advocacy into the classroom, within a model that reinforced a schoolwide focus on successful school–to–adult life transitions. Elements of the model that can be applied in other school settings are discussed.